As potencialidades da história local para o ensino de história nos anos iniciais do ensino fundamental - BELEM, Eloiza da Silva (2025)
Considering that the subject of history adds essential knowledge for the construction of socio-cultural identity and for the exercise of citizenship by students in the process of basic education, this article discusses the teaching of history in the early years of elementary school, from the perspective of valuing local history and the memory of residents of the localities in which the students live, as well as correlating the Bom Odori Festival in Tomé Açu with the teaching of local history, based on an experience report. This is a qualitative study that includes a comprehensive literature review and an essay on historical research to enhance the teaching of history in the early years of primary school. In this way, the results show that valuing local history in the early years of elementary school is of paramount importance to ensure the formation of students' socio-cultural and historical identity, because through this, students have the opportunity to learn about their own history, their ancestral roots and the traditions that continue to the present day. The conclusion is that the integration of local history into history lessons is crucial for an integral education and for the constitution of students' historical and sociocultural identities, requiring careful implementation that includes adequate teacher training and collaboration with the community.